The origin of aging: imperfectness-driven non-random damage defines the aging process and control of lifespan - Gladyshev, Vadim N. (Trends in genetics, 2013)
Physicochemical properties preclude ideal biomolecules and perfect biological functions. This inherent imperfectness leads to the generation of damage by every biological process, at all levels, from small molecules to cells. The damage is too numerous to be repaired, is partially invisible to natural selection, and manifests as aging. I propose that the inherent imperfectness of biological systems is the true root of the aging process. Because each biomolecule generates specific forms of damage, the cumulative damage is largely non-random and is indirectly encoded in the genome. I consider this concept in light of other proposed theories of aging and integrate these disparate ideas into a single model. I also discuss the evolutionary significance of damage accumulation and strategies for reducing damage. Finally, I suggest ways to test this integrated model of aging.